Marketing Logistics Systems Analysis: The Development of Heuristic Guidelines to Aid Decision Making in the Pharmaceutical Manufacturing Industry - Gregson, R. E. (Cranfield University, 1976)
This thesis describes the development of heuristic guidelines to aid logistics management in manufacturing industry, in this case pharmaceutical manufacturers, to make decisions when faced with the appraisal of alternative methods of operation. A number of research suppositions are proposed which suggest that a more formalised approach to decision making than is current practice can be implemented in assessing the total logistics costs and customer service implications of operations. A study is made of existing research in logistics and related areas, the pharmaceutical industry in general, and in particular the logistics activities of pharmaceutical manufacturers and the service requirements of their customers. A research programme is devised whose primary purpose is to enable a comparison to be made between the implications of the research suppositions and the empirical data obtained by administering questionnaires to manufacturers and samples of customers. A model of the decision making process is presented around the framework of a cost-effectiveness analysis. A systems approach is used to analyse a manufacturer's logistics operation, highlighting as it does the interactive effects between logistics activities. The research suppositions provide heuristic guidelines which relate an activity's position on a manufacturer's material flow path to that of the proposed change, and which assign service priorities in terms of lead time to customer types. These guidelines serve to decrease the number of considered interactions and, subsequently, to reduce the complexity of the analysis. A number of implications of the findings for manufacturing industry in general, for pharmaceutical manufacturers in particular, and for logistics research, are presented. Suggestions are also made to aid any company wishing to apply its own logistics systems analysis along the lines pursued in this study.